The Application of Induced Pluripotent Stem Cells Against Liver Diseases: An Update and a Review - Zhang, Lei; Pu, Ke; Liu, Xiaojun; Bae, Sarah Da Won; Nguyen, Romario; Bai, Suyang; Li, Yi; Qiao, Liang (Frontiers in Medicine, 2021)
Liver diseases are a major health concern globally, leading to poor survival and prognosis of patients which results in the need for patients to accept the main alternative of liver transplantation progressing into end-stage liver disease. Therefore, investigating the molecular mechanism of complex liver diseases and the process of pathological development has been an emerging purpose. Human induced pluripotent stem cells (hiPSCs) derived from somatic cells as an uprising alternative approach, have shown to be a possible model for studying complex liver diseases. Here, we have reviewed hiPSC technology of reprogramming and differentiation and discussed the application of hiPSCs on refractory liver diseases as well as assessing the safety of hiPSCs in clinical applications.